2016
DOI: 10.3892/ol.2016.5150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of matrine combined with cisplatin on the expression of XIAP in human rhabdomyosarcoma RD cells

Abstract: The combined effects of matrine (Mat) and cisplatin on the survival and apoptosis of rhabdomyosarcoma (RMS) RD cells, as well as the possible mechanism of the synergistic effect of Mat and cisplatin were investigated in the present study. RMS RD cells were divided and treated as follows: control group, 5 mg/l cisplatin group, Mat groups (0.5, 1.0 and 1.5 g/l), and Mat (0.5, 1.0 and 1.5 g/l) combined with 5 mg/l cisplatin groups. An MTT assay and flow cytometry were applied to detect the survival and apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…showed that MT combined with cisplatin, 5-fluorouracil, and paclitaxel, respectively, effectively inhibited the proliferation of A549 cells and showed dose-dependent anticancer effects ( Pu et al., 2018 ). It has been reported that a combination of MT and cisplatin synergistically inhibited proliferation, and induced apoptosis of rhabdomyosarcoma (RMS) RD cells, through a mechanism involving inhibition of mRNA expression of XIAP mRNA ( Li et al., 2016 ). Another study found that MT and cisplatin synergistically suppressed the growth of urothelial bladder cancer cells (EJ, T24, BIU and 5637 cells) by inhibiting the VEGF/PI3K/Akt signaling pathway ( Liao et al., 2017 ).…”
Section: Drug-drug Interactions Of Mtmentioning
confidence: 99%
“…showed that MT combined with cisplatin, 5-fluorouracil, and paclitaxel, respectively, effectively inhibited the proliferation of A549 cells and showed dose-dependent anticancer effects ( Pu et al., 2018 ). It has been reported that a combination of MT and cisplatin synergistically inhibited proliferation, and induced apoptosis of rhabdomyosarcoma (RMS) RD cells, through a mechanism involving inhibition of mRNA expression of XIAP mRNA ( Li et al., 2016 ). Another study found that MT and cisplatin synergistically suppressed the growth of urothelial bladder cancer cells (EJ, T24, BIU and 5637 cells) by inhibiting the VEGF/PI3K/Akt signaling pathway ( Liao et al., 2017 ).…”
Section: Drug-drug Interactions Of Mtmentioning
confidence: 99%
“…Matrine exhibits a wide range of pharmacological effects and has long been applied to treat viral hepatitis (6), neuropathic pain (7), isoproterenol-induced cardiotoxicity inflammatory and other diseases (8,9). In addition, increasing evidence has revealed that matrine displays anticancer effects in various cancers, such as gastric (10), rhabdomyosarcoma (11), acute myeloid leukemia (12), osteosarcoma (13), prostate (14), breast (15) and lung cancer (16). Moreover, the antitumor mechanisms of matrine have been demonstrated to involve the blockade of cell cycle progression, the induction of apoptosis, the regulation of oncogene expression, the inhibition of cytokine production and the modulation of signaling pathways (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…When Fa=0.5, isobologram analysis determined that the CI of the drugs in combination was <1.0, indicating that the two drugs had a synergistic effect. The effects of matrine and cisplatin have also been found to be synergistic in urothelial bladder cancer and rhabdomyosarcoma cells ( 21 , 39 ). Matrine may therefore increase the sensitivity of cervical cancer cells to cisplatin.…”
Section: Discussionmentioning
confidence: 99%